2013
DOI: 10.1098/rspb.2013.2448
|View full text |Cite
|
Sign up to set email alerts
|

Did postglacial sea-level changes initiate the evolutionary divergence of a Tasmanian endemic raptor from its mainland relative?

Abstract: Populations on continental islands are often distinguishable from mainland conspecifics with respect to body size, appearance, behaviour or life history, and this is often congruent with genetic patterns. It is commonly assumed that such differences developed following the complete isolation of populations by sea-level rise following the Last Glacial Maximum (LGM). However, population divergence may predate the LGM, or marine dispersal and colonization of islands may have occurred more recently; in both cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Lowered genetic diversity has also been observed when compared to mainland lineages (platypus, O. anatinus ; Furlan et al, ), which is a pattern commonly observed in island populations (Frankham, ). However, marine barriers have not influenced genetic structure for all species, such as the grey kangaroo, Macropus giganteus (Zenger, Eldridge, & Cooper, ), wedge‐tailed eagle, Aquila audax (Burridge et al, ), and white‐bellied sea eagle, Haliaeetus leucogaster (Shephard et al, ). Genetic structure (or lack‐there‐of) during comparisons of mainland and continental island populations may be influenced by several factors, including species dispersal capability and the environmental suitability of the land bridge.…”
Section: Discussionmentioning
confidence: 99%
“…Lowered genetic diversity has also been observed when compared to mainland lineages (platypus, O. anatinus ; Furlan et al, ), which is a pattern commonly observed in island populations (Frankham, ). However, marine barriers have not influenced genetic structure for all species, such as the grey kangaroo, Macropus giganteus (Zenger, Eldridge, & Cooper, ), wedge‐tailed eagle, Aquila audax (Burridge et al, ), and white‐bellied sea eagle, Haliaeetus leucogaster (Shephard et al, ). Genetic structure (or lack‐there‐of) during comparisons of mainland and continental island populations may be influenced by several factors, including species dispersal capability and the environmental suitability of the land bridge.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic isolation since the marine transgression following the LGM may induce higher probabilities of allopatric isolation between island-mainland sister species (Otte and Endler, 1989 ; Losos and Ricklefs, 2009 ). However, assumption of allopatric divergence between sister species of island and adjacent mainland since the isolation caused by the last marine transgression has been challenged (Li et al, 2010 ; Burridge et al, 2013 ). The level of allopatric divergence may be lower than expected because of prolonged gene flow between geographically isolated closely related species (Li et al, 2010 ) and also due to the recent colonization from mainland to island (Burridge et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, assumption of allopatric divergence between sister species of island and adjacent mainland since the isolation caused by the last marine transgression has been challenged (Li et al, 2010 ; Burridge et al, 2013 ). The level of allopatric divergence may be lower than expected because of prolonged gene flow between geographically isolated closely related species (Li et al, 2010 ) and also due to the recent colonization from mainland to island (Burridge et al, 2013 ). Species identification and characterization between closely related species have often been a challenge because of weak interspecific barriers.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of this cline was low (as indicated by regressions against easting and northing), but the existence of any significant pattern is indicative of some limitation to dispersal. Therefore, long-distance dispersal events, such as those implied by Ridpath and Brooker (1986) and Burridge et al (2013), are relatively uncommon within Tasmania, or are directionally biased.…”
Section: Discussionmentioning
confidence: 99%